EFEKTIVITAS LAYANAN INFORMASI BERBASIS GOOGLE CLASSROOM TERHADAP PENINGKATAN PERENCANAAN KARIR SISWA - Septiana, Rina; Astuti, Indri; Fergina, Ana (Universitas Tanjungpura, 2024)
Students who are already in senior high school should have a plan for a career they will take in the future. But what happens in the field is different. Some students in grade XI still have not fully planned the career they will choose in the future. This study was conducted to test information services based on the Google classroom to improve career planning of students in class XI social science 1 in Senior High School 5 Pontianak. The research method used was pre-experimental design. Subjects were taken based on non-probability sampling techniques with purposive sampling. The subjects were 10 students who had a very low level of career planning from a population of 38 people. The research findings showed information services based on the Google classroom are considered effective to improve career planning of students in class XI Social Sciences 1 State Senior High School 5 Pontianak. Ten students had a very low category with a percentage of 30% and two got results with a percentage of 70% in the high category.